Liposomal Delivery Systems. - Samad, Abdus (Future Science Group, 2016)
Liposomes play an important part in the safe, targeted delivery of many therapeutic and diagnostic agents. This book explores the latest developments pertaining to liposomal delivery systems with a focus on the most novel, exciting or clinically advanced research. Relevant challenges and research needs are highlighted.